2019
DOI: 10.1155/2019/4368036
|View full text |Cite
|
Sign up to set email alerts
|

Speech Technology Progress Based on New Machine Learning Paradigm

Abstract: Speech technologies have been developed for decades as a typical signal processing area, while the last decade has brought a huge progress based on new machine learning paradigms. Owing not only to their intrinsic complexity but also to their relation with cognitive sciences, speech technologies are now viewed as a prime example of interdisciplinary knowledge area. This review article on speech signal analysis and processing, corresponding machine learning algorithms, and applied computational intelligence aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 112 publications
(166 reference statements)
1
18
0
Order By: Relevance
“…Besides, it is consistent with the ideas of both a new paradigm of 21 st -century education (Cunningham, 2019) and robotics-based education (Alimisis, 2020). Interestingly, the recent developments in Speech and Language Technology (SLT), AuthorIT & TutorIT technologies have made it possible to substitute a human-run learning environment losing no instructional quality and ensuring high-cost effectiveness (Delić et al, 2019;Cernak, Asaei & Hyafil, 2018;Scandura, 2010;Scandura, 2016). The letter inspired this study and created a research gap as the study found insufficient limits of information on the use of virtual tutor's assistants in the course delivered on the Moodle platform.…”
Section: Introductionsupporting
confidence: 70%
“…Besides, it is consistent with the ideas of both a new paradigm of 21 st -century education (Cunningham, 2019) and robotics-based education (Alimisis, 2020). Interestingly, the recent developments in Speech and Language Technology (SLT), AuthorIT & TutorIT technologies have made it possible to substitute a human-run learning environment losing no instructional quality and ensuring high-cost effectiveness (Delić et al, 2019;Cernak, Asaei & Hyafil, 2018;Scandura, 2010;Scandura, 2016). The letter inspired this study and created a research gap as the study found insufficient limits of information on the use of virtual tutor's assistants in the course delivered on the Moodle platform.…”
Section: Introductionsupporting
confidence: 70%
“…5 Although N-HANS was implemented to process 16 kHz Waveform Audio File Format (WAV) for input and output, i. e., one of the most standard and broadly used audio formats, input files in other formats or sample rates are also handled through an embedded format conversion based on pysox [4], which internally transfer them into WAV format. 6 Both, single or multiple audio files organised into a directory, can be provided as an input for N-HANS, which achieves an optimal performance with GPU-acceleration 7 but is also capable of running with CPU only. To test N-HANS functionalities, a series of experiments, presented in the following, were conducted.…”
Section: Usability: Experimental Results and Evaluationmentioning
confidence: 99%
“…Two of the main procedures for enhancing audio and speech are source separation and denoising: The former aims to extract a target audio from a mixture of multiple overlapping signals [66]; the latter attempts to suppress the background noise [49,78]. With the advance of artificial intelligence, neural network based models for audio enhancement have been presented, being particularly efficient in source separation [18,20,35,36,68] and denoising [5,27,32,34,47,60,71] tasks-the performance of classic algorithms is often overtaken by artificial neural networks [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The continuous improvement of AI technology has been widely used in all walks of life, and the education field is no exception. AI simulates human listening (machine translation, speech recognition) (Delić et al, 2019), speaking (speech synthesis, human-computer dialogue) (Chiba, Nose, Kase, Yamanaka, & Ito, 2019), watching (computer vision, image recognition, text recognition) (Paglen, 2019), thinking (Theorem Proving) (Sarma & Hay, 2017), learning (machine learning, intelligent adaptive learning) (Colchester et al, 2017) and action (robot) (Khandelwal et al, 2017). In particular, AI technologies such as computer vision, natural language processing, and intelligent adaptive learning have changed traditional education and teaching (Yufei, Saleh, Jiahui, & Abdullah, 2020), and have provided universities and teachers with new ideas for teaching reform.…”
Section: Impact Of Ai In Educationmentioning
confidence: 99%